2004
DOI: 10.1093/hsw/29.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The Ambiguous Dying Syndrome

Abstract: More than one-half of the 2.4 million deaths that will occur in the United States in 2004 will be immediately preceded by a time in which the likelihood of dying can best be described as "ambiguous." Many people die without ever being considered "dying" or "at the end of life." These people may miss out on the opportunity to close important relationships and make financial and legal arrangements that can benefit themselves and their survivors. They may inadvertently forgo palliative care that is available to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…The family concerns about symptom management and decision making found by Carlson (2007) are borne out by these findings, which underscore the importance of support for advance care planning and end-stage decision making. The ambiguous nature of dying in the nursing home setting (Bern-Klug, 2004, 2006 is illustrated by the four contexts of awareness in this study and varying levels of awareness found in both staff and family members. The findings of this study replicate those of the earlier, classic study that described different scenarios of knowledge about the imminence of death among dying patients, family members, and providers (Glaser & Strauss, 1965).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The family concerns about symptom management and decision making found by Carlson (2007) are borne out by these findings, which underscore the importance of support for advance care planning and end-stage decision making. The ambiguous nature of dying in the nursing home setting (Bern-Klug, 2004, 2006 is illustrated by the four contexts of awareness in this study and varying levels of awareness found in both staff and family members. The findings of this study replicate those of the earlier, classic study that described different scenarios of knowledge about the imminence of death among dying patients, family members, and providers (Glaser & Strauss, 1965).…”
Section: Discussionmentioning
confidence: 76%
“…The majority of chronic care nursing home residents who die in these facilities do not have terminal diagnoses, primarily because the dying process is often ambiguous and not well recognized (Bern-Klug, 2004, 2006Forbes, 2001). Thus, enhanced care during the transition from routine to palliative care is important for permanent nursing home residents and their family members (Travis, Loving, McClanahan, & Bernard, 2001).…”
mentioning
confidence: 99%
“…Thus, all nursing home residents can be considered to be ''dying,'' although not imminently. The ambiguous nature of the transition to end-stage care in frail people with multiple comorbid conditions 34,35 creates a unique set of expectations for nursing home professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Staff members were asked by a clinical nurse specialist about what they wanted to know and family members were interviewed by another senior nurse to find out what was important to them when their relative was dying. The two-day workshop covered disease progression, the 'ambiguous dying syndrome' (the time before dying in which the likelihood of dying can best be described as uncertain; Bern-Klug, 2004), support for families, symptom management, making moments meaningful, last days and hours and staff care. As well as PowerPoint presentations, participants were given a work-book, discussed case studies to prompt problem solving and participated in role play.…”
Section: Discussed In Relation Tomentioning
confidence: 99%